2018
DOI: 10.1016/j.aott.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of plantar fascia is not predictive of functional outcome in plantar fasciitis treatment

Abstract: ObjectiveThe aim of this study was to define a quantitative parameter to indicate which cases of plantar fasciitis will benefit from local corticosteroid injection or ESWT and to compare the efficacy of two different treatment modalities.MethodsSeventy patients (mean age: 49.10; range: 41–58) with chronic plantar fasciitis unresponsive to conservative treatment for 3 months were treated with either betamethasone injection or extracorporeal shock wave therapy (ESWT). Correlation between AOFAS scores, fascia thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…In spite of these results, the patients showed a good clinical evolution. Similar results were reported by Ermutlu et al, 13 where the functional recovery of the patients was not associated with a normal degree of fascia thinning after treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of these results, the patients showed a good clinical evolution. Similar results were reported by Ermutlu et al, 13 where the functional recovery of the patients was not associated with a normal degree of fascia thinning after treatment.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study in the Korean population suggested that a thickness of greater than 3.8 mm was a clinically meaningful US finding of plantar fasciitis [ 8 ]. In the present study, the thickness of the plantar fascia in patients with plantar fasciitis was significantly thicker than in normal controls, but the mean thickness of the plantar fascia in patients with plantar fasciitis ( n = 109 feet) was 3.74 mm, which appears to be less thick than previously reported cases with a mean maximal thickness of 2.9 to 6.9 mm [ 6 , 7 , 33 , 34 , 35 ]. Our finding that the thickness of the plantar fascia in patients with plantar fasciitis was less than that in prior research can be attributed to the following causes.…”
Section: Discussioncontrasting
confidence: 83%
“…ESWT has been widely used as a treatment option for plantar fasciitis due to its non-invasive feature, fast recovery time and convenience for daily life of patients (10). In literature, demographic, clinical and ultrasound factors have been investigated as predictors of a better response to ESWT, with conflicting results (11)(12)(13)(14)(15)(16)(17). The aim of this study was to conduct a retrospective analysis to create models for a pre-treatment evaluation in people with plantar fasciitis, and to assess whether demographic and clinical features could be used to predict medium-term outcomes six months after focused ESWT.…”
Section: Introductionmentioning
confidence: 99%